Outcomes and toxicities in patients treated with definitive focal therapy for primary prostate cancer: systematic review. (March 2017) - Baydoun, Atallah; Traughber, Bryan; Morris, Nathan; Abi Zeid Daou, Michella; McGraw, Michael; Podder, Tarun K; Muzic, Raymond F; Lo, Simon S; Ponsky, Lee E; Machtay, Mitchell; Ellis, Rodney
Aim: This systematic review summarizes the clinical data on focal therapy (FT) when used alone as definitive therapy for primary prostate cancer (PCa).Methods: The protocol is detailed in the online PROSPERO database, registration No. CRD42014014765. Articles evaluating any form of FT alone as a definitive treatment for PCa in adult male patients were included.Results: Of 10, 419 identified articles, 10, 401 were excluded, and thus leaving 18 for analysis. In total, 2288 patients were treated using seven modalities. The outcomes of FT in PCa seem to be similar to those observed with whole gland therapy and with fewer side effects.Conclusion: Further research, including prospective randomized trials, is warranted to elucidate the potential advantages of focal radiation techniques for treating PCa.Prospero Registration Number: CRD42014014765.